Improvement in time to treatment, but not time to diagnosis, in patients with mucopolysaccharidosis type I. Issue 7 (2nd November 2020) - Giugliani, Roberto; Muschol, Nicole; Keenan, Hillary A.; Dant, Mark; Muenzer, Joseph
Abstract : Objective: Early diagnosis and treatment initiation are important factors for successful treatment of mucopolysaccharidosis type I (MPS I). The purpose of this observational study was to assess whether age at diagnosis and time to first treatment for individuals with MPS I have improved over the last 15 years. Study design: Data from the MPS I Registry (NCT00144794 ) for individuals with attenuated or severe disease who initiated therapy with laronidase enzyme replacement therapy (ERT) and/or hematopoietic stem cell transplantation (HSCT) between 1 January 2003 and 31 December 2017 were included. Results: Data were available for 740 individuals with attenuated (n=291) or severe (n=424) MPS I (unknown n=25). Median age at diagnosis for attenuated disease did not change over time and ranged between 4.5 and 6 years of age while the median duration from diagnosis to first ERT decreased from 5.6 years before/during 2004 to 2.4 months in 2014–2017. For severe MPS I treated with HSCT, median age at diagnosis was less than 1 year and median time to first treatment was less than 3 months throughout the 15-year observation period. Conclusions: Times to diagnosis and HSCT initiation for individuals with severe MPS I were consistent over time. For individuals with attenuated MPS I, the time to ERT initiation after diagnosis has improved substantially in the last 15 years, but median age at diagnosis has not improved. Efforts to improve early diagnosis in attenuated MPS I are needed to ensure that patients receive appropriate treatment at the optimal time.